1999
DOI: 10.1007/s001340050817
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer assay predicts mortality in critically ill patients without disseminated intravascular coagulation or venous thromboembolic disease

Abstract: The D-dimer assay identifies patients at increased risk for mortality and may be a more sensitive test to determine the presence of underlying microvascular pathology in critically ill patients. A positive D-dimer at admission to the MICU is associated with an increased risk for the later development of a venous thromboembolic event (VTE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…Our results corroborated with those of previous studies [21,22]. Furthermore, D-Dimer has been previously shown to a sensitive independent predictor of mortality among ICU patients [23], which was corroborated by our results. We observed that, compared to the discharge group, significantly higher proportion of patients in the death group exhibited D-Dimer > 1200 ng/mL (P = 0.023).…”
Section: Discussionsupporting
confidence: 93%
“…Our results corroborated with those of previous studies [21,22]. Furthermore, D-Dimer has been previously shown to a sensitive independent predictor of mortality among ICU patients [23], which was corroborated by our results. We observed that, compared to the discharge group, significantly higher proportion of patients in the death group exhibited D-Dimer > 1200 ng/mL (P = 0.023).…”
Section: Discussionsupporting
confidence: 93%
“…They also determined that CAP patients in PSI classes IV and V who had plasma DD levels higher than 2000 ng/mL had a higher risk of mortality 18. Some researchers have suggested that increased plasma DD levels are related to the extent of pneumonia because the PSI and APACHE II score are closely associated with the mortality rate 21. Low plasma DD levels in CAP patients (less than 500 ng/mL) at the time of admission to the hospital has been linked to a decreased likelihood of an early death or major morbidity 19.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, prothrombin activation and fibrin deposition can stimulate the extrinsic coagulation system and render the patient's blood hypercoagulable. D-Dimer is a stable and specific degradation product of cross-linked fibrin, and its increased level indicates enhanced secondary fibrinolytic activity, which can be used as one of the molecular markers of hypercoagulability and hyperfibrinolysis in vivo (34). In particular, D-dimer has been found to be well correlated with the disease activity of HSP (35).…”
Section: Discussionmentioning
confidence: 99%